2018
DOI: 10.1101/477950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential physiological role of BIN1 isoforms in skeletal muscle development, function and regeneration

Abstract: Skeletal muscle development and regeneration are tightly regulated processes. How the intracellular organization of muscle fibers is achieved during these steps is unclear. Here we focus on the cellular and physiological roles of amphiphysin 2 (BIN1), a membrane remodeling protein mutated in both congenital and adult centronuclear myopathies, that is ubiquitously expressed and has skeletal muscle-specific isoforms. We created and characterized constitutive, muscle-specific and inducible Bin1 homozygous and het… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Early work suggested that the presence of exon 11 is required to induce tubulogenesis ( Lee et al, 2002 ; Kojima et al, 2004 ), and exon 11-containing BIN1 isoforms expressed in rat, sheep, and human myocardium have indeed been observed to induce t-tubule formation ( Caldwell et al, 2014 ; De La Mata et al, 2019 ; Lawless et al, 2019 ; Li L. L. et al, 2020 ). However, other studies have reported that exon 11 is dispensable for t-tubule development ( Prokic et al, 2020 ), and shown that the mouse heart expresses four BIN1 splice variants which do not contain this motif (BIN1, BIN1+13, BIN1+17, and BIN1+13+17) ( Forbes and Sperelakis, 1976 ; Hong et al, 2014 ). In addition to gross t-tubule biogenesis, there may also be isoform-specific roles in determining their fine structure and function.…”
Section: Emerging T-tubule Regulatorsmentioning
confidence: 99%
“…Early work suggested that the presence of exon 11 is required to induce tubulogenesis ( Lee et al, 2002 ; Kojima et al, 2004 ), and exon 11-containing BIN1 isoforms expressed in rat, sheep, and human myocardium have indeed been observed to induce t-tubule formation ( Caldwell et al, 2014 ; De La Mata et al, 2019 ; Lawless et al, 2019 ; Li L. L. et al, 2020 ). However, other studies have reported that exon 11 is dispensable for t-tubule development ( Prokic et al, 2020 ), and shown that the mouse heart expresses four BIN1 splice variants which do not contain this motif (BIN1, BIN1+13, BIN1+17, and BIN1+13+17) ( Forbes and Sperelakis, 1976 ; Hong et al, 2014 ). In addition to gross t-tubule biogenesis, there may also be isoform-specific roles in determining their fine structure and function.…”
Section: Emerging T-tubule Regulatorsmentioning
confidence: 99%
“…27,28 For Bin1, full loss of BIN1 in Bin1 À/À mice is perinatally lethal, preventing the comparison with the other CNM models. 29,30 We recently created a mouse model with a skeletal muscle-specific Bin1 deletion that is viable and faithfully reproduces the decreased muscle force and most histopathological hallmarks of CNM (Bin1 mckÀ/À ; unpublished data). Herein, we focus on omics analysis of Mtm1 À/y , Bin1 mckÀ/À , and Dnm2 SL/+ mice, since they represent faithful models for the three canonical CNM forms and the mice share a similar skeletal muscle organization with patients.…”
Section: Introductionmentioning
confidence: 99%